Evaluation of pharmacist interventions on drug and dosage prescribing in pediatric settings - Angalakuditi, Mallik V. (Curtin University, 2003)
Objectives: To evaluate the influence of pharmacist interventions on drug and dosage prescribing in pediatric settings. Method: Demographic, clinical, and prescribing data and parents’ measurement data were evaluated by pre- and post studies including time series studies and control groups. The data was evaluated against Australian Therapeutic Guidelines. Educational intervention strategies were designed and administered and a post-intervention evaluation was conducted. Group comparisons were made using x2 and Student’s t-test statistics. Time series analysis involved multiple linear regression analysis. Results: The major study involved antibiotics and analgesic drugs and dosages in appendectomy in children. Significant improvements occurred in the selection and dosages of prophylactic antibiotics @<0.001) and in subsequent ward antibiotic treatments @<0.001) also showed marked conformity with the guidelines Other pediatric studies involved liquid medication dosing and prescribing accuracy for paracetamol in a developing country where a simple intervention produced very marked improvements @<0.001). An intervention in severe community-acquired pneumonia showed an improvement in the prescription of appropriate drugs @<0.001) and appropriate dosages of paracetamol (p<O.OOl) according to the guidelines. In drug utilisation evaluation of cefiriaxone, flucloxacillin and Liquigesic COB, there was a significant improvement in the dosage prescribing of ceftriaxone and flucloxacillin and no change in Liquigesic COB following the intervention. O f the total, 38/218 (17%) o f the patients received appropriate post-operative antibiotic dosages. 286/368 (78%) of the analgesic prescriptions and 31/218 (14%) of the patients on postoperative antibiotic choice and dosage that were identified as appropriate in tonsillectomy.Conclusion: This study has identified deficiencies related to the prescribing of antibiotics and analgesics in children. There was a varied level of improvement in the drug dosage prescribing of pediatricians following the pharmacist educational intervention. Locally developed guidelines are more likely to be accepted and followed than those developed nationally without local input.